Circulating human prostate cancer cells from an orthotopic mouse model rapidly captured by immunomagnetic beads and imaged by GFP expression - Kolostova, Katarina; Pinterova, Daniela; Hoffman, Robert M; Bobek, Vladimir (Anticancer research, 2011)
Circulating tumor cells (CTCs) are potential precursors of metastasis. They are also of use in diagnosing malignancy and for prognostic purposes. Our laboratory has previously isolated CTCs from orthotopic nude mouse models of human prostate cancer cells where the PC-3 cancer cells express green fluorescent protein (GFP). It was found that orthotopic tumors produced CTCs and not subcutaneous tumors, which may explain why orthotopic tumors metastasize and subcutaneous tumors do not. However, in this previous study, CTCs were observed only after culture. In the present study, using the GFP-expressing PC-3 orthotopic model and immunomagnetic beads coated with anti-epithelial cell adhesion molecule (EpCAM) and anti-prostate specific membrane antigen (PSMA), GFP-expressing CTC were isolated within 15 minutes and were readily visualized by GFP fluorescence. It was possible to immediately place the immunomagnetic-bead-captured GFP-expressing PC-3 CTCs in 3-dimensional sponge cell culture, where they proliferated. The combination of GFP expression and the use of immunomagnetic beads is a very powerful method to obtain CTCs for either immediate analysis or for biological characterization in vivo or in 3-dimensional culture.
Keywords: Animals; glutamátkarboxypeptidasa II; Green Fluorescent Proteins; Neoplastic Cells, Circulating; molekuly buněčné adheze; Lymphatic Metastasis; lymfatické metastázy; Antigens, Neoplasm; Mice, Nude; lidé; Mice; nádorové buňky kultivované; nádory prostaty; myši; Prostatic Neoplasms; zelené fluorescenční proteiny; nádorové cirkulující buňky; Tumor Cells, Cultured; Male; imunomagnetická separace; Cell Adhesion Molecules; Glutamate Carboxypeptidase II; Epithelial Cell Adhesion Molecule; Immunomagnetic Separation; zvířata; mužské pohlaví; adhezní molekula epiteliálních buněk; antigeny nádorové; myši nahé; Humans